Ma’ālimu al-Fikr al-Islāmī qabl Ẓuhūr al-Ittijāh al-Salafī bi Indūnīsīyā - Zarkasyi, Amal Fathullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
After Sunni had triumphed over Shi'i, a new conflict arose between philosophical Tasawuf and pantheism. The dominant figures in the pantheist camp included ?amzah al-Fan?uri and Shams al-D?n al-Sumatrani. This madhhab was supported by the elites in the Aceh Kingdom. Shaykh Nur al-Din al-Raniri and Shaykh 'Abd al-Ra'uf al-Singkili introduced Sunni Tasawuf into the kingdom in order to eradicate philosophical Tasawuf in influence. In the end, Shaykh Nur al-Din al-Raniri and Shaykh 'Abd al-Ra'uf succeeded in annihilating philosophical Tasawuf. DOI: 10.15408/sdi.v16i3.476